2015
DOI: 10.1111/hel.12204
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection of Helicobacter pylori and its Antimicrobial Resistance in Brazzaville, Congo

Abstract: Therefore, the use of standard clarithromycin-based triple therapy is still possible as an empiric first-line treatment as well as prescription of bismuth-based quadruple therapy, which includes tetracycline, but not a levofloxacin-based triple therapy because of the high rate of resistance to fluoroquinolones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
29
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 26 publications
(57 reference statements)
5
29
4
Order By: Relevance
“…Our study allowed for describing a high prevalence (97.43%) of H pylori infection by molecular testing in Mauritanian patients with upper gastrointestinal symptoms. This rate agrees with previous findings in African countries such as the Congo and Senegal 32,33 . However, the prevalence of H pylori infection in Mauritania is not reflected by our results because asymptomatic individuals were not included.…”
Section: Discussionsupporting
confidence: 91%
“…Our study allowed for describing a high prevalence (97.43%) of H pylori infection by molecular testing in Mauritanian patients with upper gastrointestinal symptoms. This rate agrees with previous findings in African countries such as the Congo and Senegal 32,33 . However, the prevalence of H pylori infection in Mauritania is not reflected by our results because asymptomatic individuals were not included.…”
Section: Discussionsupporting
confidence: 91%
“…Lehours did not find a difference between gastritis and gastric MALT lymphoma patients regarding H. pylori Open Journal of Medical Microbiology pathogenicity factors [20]. Our results can be explained by the fact that H. pylori is acquired early in childhood, as there is no statistically significant difference between the age groups and the strains exist in many parts of the population, even if the results of the endoscopy are normal [41].…”
Section: Discussioncontrasting
confidence: 47%
“…According to Graham et al [119] , in the presence of fluoroquinolone resistance treatment success with quinolone-containing therapy decreases and these results can be predicted using a formula. A report published in United States in 2015 determined that the prevalence of levofloxacin resistance was 31.3% (95%CI: 23.1%-39.4%) [120] and another study showed a high rate of quinolone resistance (50%) in Congo [121] . We calculated the effect of quinolone resistance on treatment success using the proposed formula, which indicated success rates of 87.6% and 73.5%, respectively [119,122] .…”
Section: Quinolones To Existing Treatmentmentioning
confidence: 99%